2008
DOI: 10.1080/15560350802081264
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Substance-use Treatment: Service Delivery, Research on Effectiveness, and Emerging Treatment Alternatives

Abstract: Adolescent substance use remains a persistent and serious problem in society despite use patterns showing consistent declines in alcohol and other illicit drug use since 2000. This paper provides an overview of the somewhat confusing landscape of substance-use treatment options available to families and professionals seeking treatment services. A case study is presented illustrating one treatment option, termed outdoor behavioral healthcare, to highlight one example of alternative treatment and educational pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Previous studies showed the effectiveness of specific private pay WT programs (Bandoroff 1992;Clark et al 2004;Davis-Berman and Berman 1989;Eikenoes et al 2006;Harper 2009;Harper and Russell 2008;Harper et al 2007;Pawlowski et al 1993;Ronalds and Allen-Craig 2008;Russell 2003Russell , 2005Russell , 2007, but no meta-analyses to date have drawn definitive conclusions about the treatment type as a whole for private pay clients.…”
Section: Implications For Practicementioning
confidence: 99%
“…Previous studies showed the effectiveness of specific private pay WT programs (Bandoroff 1992;Clark et al 2004;Davis-Berman and Berman 1989;Eikenoes et al 2006;Harper 2009;Harper and Russell 2008;Harper et al 2007;Pawlowski et al 1993;Ronalds and Allen-Craig 2008;Russell 2003Russell , 2005Russell , 2007, but no meta-analyses to date have drawn definitive conclusions about the treatment type as a whole for private pay clients.…”
Section: Implications For Practicementioning
confidence: 99%
“…Further, this novel approach is focused on delivering therapeutic services to a high-risk population, young adults with SUDs. While some studies of wilderness therapy have explored reductions in substance abuse and dependence as an outcome of treatment (Bettmann, Russell, & Parry, 2014;Russell, 2007), this author is unaware of any prior investigation of therapeutic effectiveness of S-OBH specifically, in which participants with primary SUDs engage in treatment which includes components of both OBH and residential substance abuse treatment (i.e., drug and alcohol rehabilitation programming) and when recovery from substance dependence is the primary outcome of interest.…”
Section: Jtsp • 109mentioning
confidence: 99%
“…Positive physiological outcomes have also been found (DeMille et al 2014). In addition, OBH appears to be effective for a variety of populations and problems, including adolescents in the Juvenile Justice system (Jones et al 2004;Russell 2005a;Wright 1983), adolescent sex offenders (Gillis and Gass 2010;Lambie et al 2000), and adolescents with various diagnosable disorders (Clark et al 2004;Russell 2006, Russell 2008). …”
Section: Outdoor Behavioral Healthcarementioning
confidence: 99%